PENGARUH LEADERSHIP DAN WORK MOTIVATION TERHADAP KINERJA KARYAWAN : (LITERATURE REVIEW MANAJEMEN KINERJA) - Lintang Nareswarajati; Septia Nur Rachma; Zelika Fatatun Malikhatun; Dani Rizana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the influence of leadership and motivation on the workforce. Leadership and motivation are two important factors that affect the performance, productivity, and welfare of the workforce. The research method used is a systematic literature review (SLR) by collecting data from various literature sources. The results of the literature review indicate that effective leadership, such as leadership style, contributes to increased engagement, performance, and workforce satisfaction. In addition, high motivation significantly affects employee morale, productivity, and commitment to the organization. This study concludes that a combination of inspirational leadership and the right motivational strategies can create a conducive work environment, improve workforce performance, and support the achievement of organizational goals.